A Cross-Sectional Study on Perceived Organizational Support Moderating Career Development Practices and Work Engagement in Nepalese Commercial Banks - Kharel, Shreekrishna; Niraula, Ganesh Prasad (Nepal Journal of Multidisciplinary Research, 2025)
Background: Work engagement is vital for organizational performance, but its relationship with career development in developing-country banking remains underexplored. This study investigates that relationship, with perceived organizational support (POS) as a moderating variable, in Nepalese commercial banks. Methods: Cross-sectional data were collected from 410 bank employees across eight commercial banks using stratified random sampling. Partial Least Squares Structural Equation Modelling (Smart-PLS) was employed to evaluate the proposed model and hypotheses. While construct reliability and validity were established through the assessment of convergent and discriminant validity. Results: The results indicate that training and development, managerial coaching and talent management are significantly associated with work engagement. Furthermore, the POS moderates the relationships between training and development, managerial coaching, and talent management with work engagement. Conclusion: The study concludes that career development practices—training and development, managerial coaching, and talent management—play a vital role in enhancing work engagement in Nepalese commercial banks. While POS showed limited moderating effects, the results underscore the importance of strategically designed career development practices to foster engagement in developing economy contexts. Novelty: This study provides novel evidence by examining POS as a moderator between career development practices and work engagement in Nepalese commercial banks, extending the Job Design-Resource model and contributing context-specific insights from a developing economy.